Concurrent Reactivation of Herpes Simplex and Varicella Zoster Viruses Confirmed by the Loop-Mediated Isothermal Amplification Assay - Tsukane Kobayashi; Akiko Yagami; Kayoko Suzuki; Tetsushi Yoshikawa; Kayoko Matsunaga (Karger Publishers, 2014)
Concurrent reactivation of herpes simplex and varicella zoster viruses is rare. Here, we describe the case of an elderly patient with herpes labialis and herpes zoster manifesting as a right-side facial eruption with vesicles and crusting. The loop-mediated isothermal amplification (LAMP) assay demonstrated the presence of both herpes simplex virus type 1 and varicella zoster virus in swab samples taken from the face, which was confirmed by real-time PCR, suggesting concurrent reactivation of both viruses. The use of the LAMP assay in the present case indicates its usefulness in the diagnosis of atypical herpes infections.